Arkeologi Prostitusi di Kawasan Lampu Merah Jelakeng, Batavia: Arkeologi Prostitusi di Kawasan “Lampu Merah” Jelakeng, Batavia - Wantania, Christoffer; Daud Aris Tanudirjo (BRIN, 2024)
Prostitution is a social phenomenon that has long existed in many places, including Indonesia. However, this issue has hardly been studied in Indonesian archaeology. This paper discusses the results of a preliminary archaeological study of prostitution in the Jelakeng area, a “redlight district“as known as prostitution localisation in Batavia during the colonial period. This pilot study aims to reveal how archaeological remains in the Jelakeng area maintain the image of Jelakeng as a ‘’redlight district”. Should the existing remains to be preserved? This study was conducted through observations, interviews, and literature review. The archaeological remains in the Jelakeng are too limited to maintain the image of a “redlight district’’. However, the collective memory of this area is still strong enough to establish its significance as a ‘’redlight district’’ since at least the mid-18th century. The limited archaeological remains and documentation of this area is a challenge for the application of archaeology of prostitution to find more evidence of the colonial subculture that developed in this area. It can potentially to reveal various socio-cultural aspects that have been